アイスコア連続融解分析装置（CFA）によるグリーンランド浅層コアの分析 - 東, 久美子; Azuma, Kumiko (2016)
アイスコア研究センターでは数年かけてアイスコア連続融解分析装置（CFA)を開発してきた。この装置を用い、SGIMAプロジェクトの下でグリーンランドにおいて掘削した浅層コア(SIGMA-Dコアコア）を分析した。CFAの概略と、ブラックカーボン等の分析の初期結果を報告する。 A continuous flow analysis (CFA) system has been developed at the Ice Core Research Center of NIPR. A shallow ice core (SIGMA-D core) drilled in Greenland under the SIGMA project was analyzed with the NIPR CFA system. Outline of the CFA system and preliminary results of the analyses including back carbon data will be presented. Polar Meteorology and Glaciology Group seminar / 気水圏コロキウム 日時：6月15日（水）10:00-10:50 場所：C301（3階セミナー室） conference object